2012
DOI: 10.1097/nmd.0b013e318247cb6d
|View full text |Cite
|
Sign up to set email alerts
|

Women Respond More Favorably to Transference Intervention Than Men

Abstract: The present study focuses on whether there is a sustained difference in treatment response to transference interventions between women and men. Data from the First Experimental Study of Transference Interpretations were used. One hundred patients were randomized to receive dynamic psychotherapy in 1 year with either a moderate level of transference intervention or no transference intervention. Follow-ups were 1 year and 3 years after treatment termination. The two primary outcome measures were the Psychodynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In patients with more mature object relations and a good alliance, a negative effect of transference interpretations was found. In this analysis furthermore women benefited significantly more from transference interpretations than men (Ulberg et al, 2012). It is of importance that these data come from studies in diagnostically heterogeneous patient samples and therefore are not specific to patients with depression.…”
Section: Discussionmentioning
confidence: 90%
“…In patients with more mature object relations and a good alliance, a negative effect of transference interpretations was found. In this analysis furthermore women benefited significantly more from transference interpretations than men (Ulberg et al, 2012). It is of importance that these data come from studies in diagnostically heterogeneous patient samples and therefore are not specific to patients with depression.…”
Section: Discussionmentioning
confidence: 90%
“…There was an interaction between patient gender and QOR: a strong positive effect of transference work among female patients with low QOR scale scores appeared, versus a negative effect of transference work for male patients with high Downloaded by [The University of Manchester Library] at 04:59 25 November 2014 QOR scale scores. The subgroup of women with poor interpersonal functioning had a particularly strong effect of dynamic psychotherapy with transference work (Ulberg, Johansson, Marble, & Høglend, 2009;Ulberg, Høglend, Marble, & Johansson, 2012).…”
Section: Transference Work and Gender Differences At Posttreatmentmentioning
confidence: 99%
“…Our FEST investigations have shown that patients with a life‐long pattern of poor relational functioning profit from therapy with TI, and that woman responded better to TI than men (Høglend et al., ). In particular, women with difficult relational functioning improved most from therapy with TI (Ulberg, Høglend, Marble, & Johansson, ).…”
Section: In‐session Processmentioning
confidence: 99%